Beam shifts in two-dimensional atomic crystals. (18th November 2021) - Ling, Xiaohui; Zhang, Zan; Chen, Shizhen; Zhou, Xinxing; Luo, Hailu
Abstract: Optical beam shifts, which mainly refer to the Goos–Hänchen shift and spin-Hall shift, widely exist in basic optical processes such as interface reflection and refraction. They are very sensitive to changes in the parameters of the materials that constitute the interface and therefore show great potential for applications in precision metrology and sensing. The interaction between light and two-dimensional (2D) atomic crystals is very weak, and beam shifts provide an alternative approach to explore and characterize 2D atomic crystals. In this paper, we first present a full-wave theory of beam shifts and introduce the experimental measurement of beam displacements with quantum weak measurement technology, and then review their applications in characterizing 2D atomic crystals, such as determining the layer number and measuring the optical conductivity of few-layer graphene. Finally, we discuss the beam displacements in twisted bilayer 2D atomic crystals and 2D atomic crystals under applied electric or magnetic fields.